Caracterización de residuos sólidos y propuesta técnica para transporte y rutas de recolección en la Parroquia San Luis, Cantón Riobamba - Unach (2019)
The San Luis parish is located in the inter-Andean region at 2662 masl, its climate is temperate sub-Andean, it is located at a distance of 2 km from Riobamba, it has a population of 12055 inhabitants according to the last population census (INEC, 2010). As background in the parish the socio-economic situation of the inhabitants is unknown, the quantity and characteristics of the solid waste generated; which leads to the collection service being deficient. This research is based on the following: "Methods of urban characterization and socioeconomic characterization of the city of Riobamba" (UNACH,ICITS,2013), M.Sc. Ing. Alfonso Arellano. The were identified, whit the highest economic capacity B with 46.43%; C with 39.29% and the lowest capacity D with 14.28%. In the first stage, 28 dwellings were randomly selected, the sampling was carried out for 7 days from August 5 to 11, 2018. From this sample, the per capita production, components, pH, organic matter and humidity were determined. The average per capita production (PPC) of urban solid waste (RSU) is: for stratum B 0.51 kg / inhabitant / day, stratum C 0.89 kg / inhabitant / day and stratum D 0.52 kg / room / day The average PPC of the San Luis parish is 0.66 kg / inhabitant / day. 62% of the solid waste produced corresponds to organic matter; in addition, other potentially recyclable components represented with 38% were determined; of which the highest production are: plastics (fine, coarse and bottles) with 9.30%; and the 6.55% corresponding to paper, tetrapac and cardboard. The average density of the parish head is 274.58 kg / m3. The proposal elaborated for transport and collection routes takes into account the per capita production (PPC) of the population of the parish head which is 0.66 kg / inhab / day, after that the daily production is obtained that is equal to 4, 62 m3; These data allow to define the volume of the vehicle for the transport of solid waste, and at the same time optimize the current collection system using a solid waste classification program.